Sudden deaths from positional asphyxia: A case report. Issue 24 (June 2018) - Chmieliauskas, Sigitas; Mundinas, Eimantas; Fomin, Dmitrij; Andriuskeviciute, Gerda; Laima, Sigitas; Jurolaic, Eleonora; Stasiuniene, Jurgita; Jasulaitis, Algimantas
Abstract: Rationale: Positional asphyxia is a rare cause of sudden death and a difficult diagnosis, based mostly on the circumstances of the incident, along with particular external and internal findings, frequent in asphyxia (signs of sudden death). Patient concerns: In this report, we are describing one case of adult who was found positioned in a way that led to eventual asphyxiation. Diagnoses: The final diagnosis of positional asphyxia was determined after the autopsy. Interventions: In a head-down position, gravitation and mechanical forces lead to an increased pressure on the diaphragm from the weight of the abdominal organs. Abdominal breathing, and later, chest breathing were hindered by the raised diaphragm and the difference between abdominal and breathing pressures. Outcomes: It is known that death from positional asphyxia can emerge in several ways, such as the external breathing suppression when the victim's torso is compressed or deformed. Lessons: Therefore, the current criteria for positional asphyxia are based on the obstruction of normal gas exchange caused by the body position, the impossibility to move to another position, and the exclusion of other causes of death. The forensic medical examination must also be started at the scene of the incident.